Spin in dental publications: a scoping review - Laís Rueda CRUZ; Stephanie Fumagalli BRAGA; Paulo NADANOVSKY; Ana Paula Pires dos SANTOS (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract The aim of this review was to map the practice of spin in scientific publications in the dental field. After registering the review protocol (osf.io/kw5qv/), a search was conducted in MEDLINE via PubMed, CENTRAL, Embase, Scopus, LILACS, ClinicalTrials.gov, and OpenGrey databases in June 2023. Any study that evaluated the presence of spin in dentistry was eligible. Data were independently extracted in duplicate by two reviewers. After removing duplicates, 4888 records were screened and 38 were selected for full-text review. Thirteen studies met the eligibility criteria, all of which detected the presence of spin in the primary studies, with the prevalence of spin ranging from 30% to 86%. The most common types of spin assessed in systematic reviews were failure to mention adverse effects of interventions and to report the number of studies/patients contributing to the meta-analysis of main outcomes. In randomized controlled trials, there was a focus on statistically significant within-group and between-group comparisons for primary or secondary outcomes (in abstract results) and claiming equivalence/noninferiority/similarity for statistically nonsignificant results (in abstract conclusions). The practice of spin is widespread in dental scientific literature among different specialties, journals, and countries. Its impact, however, remains poorly investigated.